2009
DOI: 10.1016/j.expneurol.2009.02.015
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial permeability transition pore in motor neurons: Involvement in the pathobiology of ALS mice

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease of motor neurons (MNs) that causes paralysis. Some forms of ALS are inherited, caused by mutations in the superoxide dismutase-1 (SOD1) gene. The mechanisms of human mutant SOD1 (mSOD1) toxicity to MNs are unresolved. Mitochondria in MNs might be key sites for ALS pathogenesis, but cause-effect relationships between mSOD1 and mitochrondiopathy need further study. We used transgenic mSOD1 mice to test the hypothesis that the mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
249
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 160 publications
(262 citation statements)
references
References 97 publications
10
249
3
Order By: Relevance
“…Indeed, CypD deletion studies show benefit in mouse models of amyloid lateral sclerosis and Parkinson's diseases as genetic ablation of CypD delayed the onset of disease and extended lifespan (Martin, Semenkow, Hanaford, & Wong, 2014; Martin et al., 2009), strengthening the role of the mPTP in the mechanisms of both diseases. The beneficial effect observed with a novel small mPTP inhibitor in a mouse model of amyloid lateral sclerosis confirmed that the mPTP could represent an interesting target for drug development in amyloid lateral sclerosis (Martin, Fancelli, et al., 2014).…”
Section: Evidence For the Involvement Of Mptp Opening In Age‐associatmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, CypD deletion studies show benefit in mouse models of amyloid lateral sclerosis and Parkinson's diseases as genetic ablation of CypD delayed the onset of disease and extended lifespan (Martin, Semenkow, Hanaford, & Wong, 2014; Martin et al., 2009), strengthening the role of the mPTP in the mechanisms of both diseases. The beneficial effect observed with a novel small mPTP inhibitor in a mouse model of amyloid lateral sclerosis confirmed that the mPTP could represent an interesting target for drug development in amyloid lateral sclerosis (Martin, Fancelli, et al., 2014).…”
Section: Evidence For the Involvement Of Mptp Opening In Age‐associatmentioning
confidence: 97%
“…mPTP opening also plays a role in the neuronal injury relevant to neurodegenerative diseases increasing in aging populations such as Alzheimer's, Parkinson's, and amyloid lateral sclerosis diseases ( Angelova & Abramov, 2017; Du et al., 2008; Gandhi et al., 2009; Martin et al., 2009 ). This is particularly true for Alzheimer's disease which is characterized by the presence of extracellular senile plaques, mainly composed of amyloid‐β (Aβ) peptide and intracellular neurofibrillary tangles made up of hyperphosphorylated tau protein (Selkoe, 2004).…”
Section: Evidence For the Involvement Of Mptp Opening In Age‐associatmentioning
confidence: 99%
“…We next assessed the possible role of MPTP in in vivo Pdx1 +/− β-cell death using a functional read-out, phenotypic rescue. CypD is an essential component of the MPTP, and genetic ablation of the peptidyl-prolyl isomerase (Ppif) gene encoding CypD prevents MPTP-dependent cell death (12,13,19). Accordingly, we crossed Pdx1 +/− mice, which have a well-described phenotype of glucose intolerance associated with decreased β-cell mass (4,(8)(9)(10)16), onto the homozygous Ppif −/− background.…”
Section: Primary Mitochondrial Abnormalities Inmentioning
confidence: 99%
“…Finally, opening of the mitochondrial permeability transition pore (MPTP) is the irreversible step in programmed necrosis. The latter process plays an important role in the pathogenesis of Alzheimer's disease and amyotrophic lateral sclerosis (12,13).…”
mentioning
confidence: 99%
“…Chronic diseases in which MPTP-dependent programmed cell death has been implicated include Alzheimer's disease, 30 muscular dystrophy, 31 amyotrophic lateral sclerosis, 62 heart failure, 33 and diabetes. 32 It is likely that this list will expand further.…”
Section: Discussionmentioning
confidence: 99%